Micron-Scale Deformation: A Coupled In Situ Study of Strain Bursts and Acoustic Emission. (17th October 2017) - Hegyi, Ádám István; Ispánovity, Péter Dusán; Knapek, Michal; Tüzes, Dániel; Máthis, Kristián; Chmelík, František; Dankházi, Zoltán; Varga, Gábor; Groma, István
Abstract: Plastic deformation of micron-scale crystalline materials differs considerably from bulk samples as it is characterized by stochastic strain bursts. To obtain a detailed picture of the intermittent deformation phenomena, numerous micron-sized specimens must be fabricated and tested. An improved focused ion beam fabrication method is proposed to prepare non-tapered micropillars with excellent control over their shape. Moreover, the fabrication time is less compared with other methods. The in situ compression device developed in our laboratory allows high-accuracy sample positioning and force/displacement measurements with high data sampling rates. The collective avalanche-like motion of the dislocations is observed as stress decreases on the stress–strain curves. An acoustic emission (AE) technique was employed for the first time to study the deformation behavior of micropillars. The AE technique provides important additional in situ information about the underlying processes during plastic deformation and is especially sensitive to the collective avalanche-like motion of the dislocations observed as the stress decreases on the deformation curves.